Identity and Guilt as Mediators of Pro-environmental Spillover - Truelove, Heather Barnes; Carrico, Amanda R.; Yeung, Kam Leung; Wolff, Jennifer M. (Frontiers in Psychology, 2021)
Policymakers are interested in programs that increase targeted pro-environmental behavior (PEB) and spill over to increase non-targeted PEBs. Theoretically, guilt should lead to negative spillover and identity to positive spillover, though this has rarely been tested empirically. Additionally, little is known about how reminders of past PEB behavior might also lead to downstream spillover effects . Across two studies, participants (Study 1: 377 MTurk workers; Study 2: 172 undergraduates) were randomly assigned to write about a prior PEB, an anti-environmental behavior, or to a control condition. Subsequently, respondents were given an opportunity to perform a PEB2 and completed measures of PEB3 intentions. Results showed some evidence of positive (through increasing identity) and negative (through decreasing guilt) indirect spillover pathways from prior PEB reminders to PEB2 performance and PEB3 curtailment intentions (but not efficiency upgrade intentions). However, there were no overall spillover effects from PEB reminders to PEB2 performance or PEB3 intentions, as the positive and negative indirect effects cancelled each other out. Results also showed positive spillover from PEB2 performance to PEB3 curtailment intentions through increasing environmental guilt. The strength of the spillover effects depended on the comparison group for the experimental manipulation, whether environmental guilt or global guilt was measured, and the type of PEB. The results suggest that environmental communications that remind people of their prior PEB may not meaningfully spill over to further PEB performance or intentions.